Global governance of coastal ecosystems, the making of blue carbon: Co-production, abstraction and enactment - Thoni, Terese; Rummukainen, Markku (Sustainable environment, 2025)
The enhancement and protection of coastal ecosystems that sequester carbon for climate change mitigation have developed over the last 15 years, and today are part of climate governance. After an initially challenging start in terms of policy interest, Blue Carbon is now included in some countries’ national inventories, and as such, enters the global sums of emissions and sinks, and becomes relevant for market-based mechanisms. This study focuses on how these ecosystems were made governable as carbon sources. This making of Blue Carbon can be seen as a global governance object drawing on the co-production of science and policy. It needs to be understood as both a part of and the result of the broader climate change policy envelope. The application of standardization and the process of making values visible and invisible have been important, inherently building on the idea that the carbon flows of these ecosystems can be managed. They are also subject to their natural actions and responses, and the question of how to manage them if they become greenhouse gas emission sources is left unanswered. Likewise, when Blue Carbon becomes an element of global climate governance in terms of carbon, it blurs the conservation and climate adaptation dimensions of the same systems, which may not be conducive to effective action minding risks and leveraging synergies. Increased plurality in the meaning-making process, with a greater focus on relationality and across policy arenas, could be a way to develop alternative governance mechanisms for coastal ecosystems.